2012
DOI: 10.1038/onc.2012.457
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β phosphorylation of the KLF6 tumor suppressor promotes its transactivation of p21

Abstract: KLF6, a ubiquitously expressed Krüppel-like transcription factor, is frequently inactivated in human cancer and has significant roles in cellular proliferation, apoptosis, differentiation and development. A key mechanism of KLF6-mediated growth suppression is through p53-independent transactivation of p21. Several cancer-derived KLF6 mutants lead to the loss of p21-mediated growth suppression through an unknown mechanism. Because several colorectal cancer and hepatocellular carcinoma-derived KLF6 mutations aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Apoptosis and cellular stress, which are key features of NAFLD, are also closely linked to p53 activity, and thus p53 is an increasing focus in NAFLD research [27]. On a regulatory level, glycogen synthase kinase (GSK3) activation promotes hepatocyte lipoapoptosis, a key feature of NAFLD, and we previously demonstrated that GSK3β directly phosphorylates KLF6, and thus increases its growth suppressor properties in vitro [28, 29]. PPARα, which we identify here as a KLF6-regulated protein, is critical for the development of hepatic steatosis associated with hepatitis C infection, a major risk factor for hepatocellular carcinoma (HCC) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis and cellular stress, which are key features of NAFLD, are also closely linked to p53 activity, and thus p53 is an increasing focus in NAFLD research [27]. On a regulatory level, glycogen synthase kinase (GSK3) activation promotes hepatocyte lipoapoptosis, a key feature of NAFLD, and we previously demonstrated that GSK3β directly phosphorylates KLF6, and thus increases its growth suppressor properties in vitro [28, 29]. PPARα, which we identify here as a KLF6-regulated protein, is critical for the development of hepatic steatosis associated with hepatitis C infection, a major risk factor for hepatocellular carcinoma (HCC) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MST1 could negatively regulated Akt activity and thereby promote GSK3β [25, 26], which could activate p21 [27]. So, the repression of p21 after KCTD11 knock-down in Huh7 could be a result of up-regulated MST1/GSK3β.…”
Section: Resultsmentioning
confidence: 99%
“…KLF6 plays a key role in cell cycle regulation, differentiation and apoptosis (Lang et al;Bieker;Mallipattu et al, 2015). Furthermore, it has been shown that functional inactivation of KLF6 in various types of cancers such as prostate, ovary and colon, is caused by somatic mutations, loss of heterozygosity (LOH) and silencing by hypermethylation of its promoter Cho et al, 2006;Sangodkar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…KLF6 has great importance in the control of various processes as cell growth, cell differentiation, apoptosis and angiogenesis (Gehrau et al, 2011;Lang et al, 2013). In relation to its function, it is known that KLF6 is a tumor suppressor, also inactivation either by loss of heterozygosity (LOH), somatic mutation or methylation of its promoter, leads to the development of various types of cancers such as prostate, colon, gliomas and hepatocellular carcinoma (Di Feo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%